STUDI LITERATUR PEMAHAMAN KONSEP PEMBELAJARAN MATEMATIKA PESERTA DIDIK MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) - Rini, Eva Setya (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2021)
The purpose of this paper is to describe the ability to understand students' mathematical learning conceptsthrough a problem-based learning model (PBM). This research is a literature study with the data collectionmethod taking data from published scientific journals. The scientific journals that have been collected arethen analyzed and identified. Based on the results of the analysis and identification, it was found that theunderstanding of students' mathematics learning concepts increased through the application of problem-based learning models (PBM) so that the effect on learning outcomes was getting better, seen from the scoreof students' understanding of mathematics learning concepts which was increasing.